Identification of Novel BRCA1 and RAD50 Mutations Associated With Breast Cancer Predisposition in Tunisian Patients - Mighri, Najah; Hamdi, Yosr; Boujemaa, Maroua; Othman, Houcemeddine; Ben Nasr, Sonia; El Benna, Houda; Mejri, Nesrine; Labidi, Soumaya; Ayari, Jihen; Jaidene, Olfa; Bouaziz, Hanen; Ben Rekaya, Mariem; et al. (Frontiers in Genetics, 2020)
Background Deleterious mutations on BRCA1/2 genes are known to confer high risk of developing breast and ovarian cancers. The identification of these mutations not only helped in selecting high risk individuals that need appropriate prevention approaches but also led to the development of the PARP-inhibitors targeted therapy. This study aims to assess the prevalence of the most frequent BRCA1 mutation in Tunisia, c.211dupA, and provide evidence of its common origin as well as its clinicopathological characteristics. We also aimed to identify additional actionable variants using classical and next generation sequencing technologies (NGS) which would allow to implement cost-effective genetic testing in limited resource countries. Patients and Methods Using sanger sequencing, 112 breast cancer families have been screened for c.211dupA. A set of patients that do not carry this mutation have been investigated using NGS. Haplotype analysis was performed to assess the founder effect and to estimate the age of this mutation. Correlations between genetic and clinical data have been also performed. Results The c.211dupA mutation has been identified in 8 carriers and a novel private BRCA1 mutation, c.2418dupA, has been identified in one carrier. Both mutations are likely specific to North-Eastern Tunisia. Haplotype analysis confirmed the founder effect of c.211dupA and showed its recent origin. Phenotype-genotype correlation showed that both BRCA1 mutations seem to be associated with a severe phenotype. Whole Exome Sequencing (WES) analysis of a BRCA negative family revealed a Variant of Unknown Significance, c.3647C>G on RAD50. Molecular modeling showed that this variant could be classified as deleterious as it is responsible for destabilizing the RAD50 protein structure. Variant prioritization and pathway analysis of the WES data showed additional interesting candidate genes including MITF and ANKS6. Conclusions We recommend the prioritization of BRCA1-c.211dupA screening in high risk breast cancer families originating from the North-East of Tunisia. We also highlighted the importance of NGS in detecting novel mutations, such as RAD50-c.3647C>G. In addition, we strongly recommend using data from different ethnic groups to review the pathogenicity of this variant and reconsider its classification in ClinVar.